IMPLEMENTASI STRATEGI KOMUNIKASI CSR PT PERTAMINA EP LIMAU FIELD PADA PROGRAM GEMA STUNTING - Syarafina, Mutiara; Adli, Adli (Universitas Teuku Umar, 2025)
This study aims to analyze the implementation of communication strategies in the Corporate Social Responsibility (CSR) program of PT Pertamina EP Limau Field through the Synergy Community Movement for Stunting (GEMA STUNTING) initiative in Rambang Niru District, Muara Enim Regency, South Sumatra. This program is the company's response to the problem of stunting which is still a public health challenge in Indonesia. Through a descriptive qualitative approach, data is collected through interviews, observations, and documentation with parties involved such as companies, health center cadres and beneficiaries of the program. The results of the study show that the communication strategy applied includes 4 elements, namely, (1) Understanding the Audience, (2) Compiling the Message, (3) Identifying Methods, (4) Choosing and Utilizing Media. In this strategy, the communication approach chosen is participatory, which involves various local stakeholders such as the village government, posyandu cadres, health centers, and community leaders. They are involved at every stage of the program, from the identification process to implementation, so as to allow for two-way communication that supports information clarity and active community involvement.